PERACANGAN RINTISAN BISNIS DIGITAL POTOSHARE INDONESIA PLATFORM UNTUK MONETISASI KARYA SENI DIGITAL - Firdaus; Muhammad Rizky Dwiputra; Siti Nurlela (INTI Nusa Mandiri, 2026)
Digital Transformation in the creative economy sector has opened up opportunities for industry players, especially photographers, in distributing and monetizing digital artworks more widely. However, many photographers still have limitations in marketing their products, especially because there are no local platforms that focus on and support digital product sales systems such as portfolio management, digital transactions based on these problems, this study aims to design a digital business in the form of a web-based platform called Potoshare Indonesia, which is intended as a digital marketplace that specializes in photography and digital artwork products such as photos, presets, e-books, and building a professional online portfolio. The method used in this study uses the Rational Unified Process (RUP) approach and business modeling using the Business Model Canvas (BMC). The results of this study are the design of digital business applications and strategies that are considered feasible and have great potential for further development. Potoshare Indonesia is expected to be a digital solution that supports the growth of the creative economy in the focused of photography.